Energy-saving H2 production from a hybrid acid/alkali electrolyzer assisted by anodic glycerol oxidation. Issue 35 (30th August 2022) - Liu, Bowen; Wang, Genxiang; Feng, Xin; Dai, Ling; Wen, Zhenhai; Ci, Suqin
Abstract : A hybrid acid/alkali electrolyzer is assembled by coupling the prepared Cu–Cu2 O/CC anode for the GOR in alkali with a commercial Pt/C cathode for the HER in an acid, which only requires an applied voltage of 0.59 V to reach 10 mA cm −2 for H2 and formate production. Abstract : Water electrolysis is a promising technology for efficient hydrogen production, but it has been heavily hindered by the sluggish kinetics and high potential of the anodic oxygen evolution reaction (OER). Replacing the OER with the glycerol oxidation reaction (GOR) at the anode is recognized as a potential strategy to address this issue. In this work, the self-supported electrocatalytic electrode of Cu–Cu2 O nanoclusters on carbon cloth (Cu–Cu2 O/CC) is fabricated for the electrocatalysis of the GOR, which has high activity towards the GOR, reaching 10 mA cm −2 at an applied voltage of 1.21 V, and shows high selectivity for formate production with a faradaic efficiency (FE) of over 80% in a wide potential range. Moreover, a hybrid acid/alkali electrolyzer is assembled by coupling the Cu–Cu2 O/CC anode for the GOR in an alkaline electrolyte with commercial Pt/C as the cathode for the hydrogen evolution reaction (HER) in an acid electrolyte. The dual-electrolyte electrolytic cell only requires an applied voltage of 0.59 V to reach 10 mA cm −2 with a FE of ∼100% for H2 and 97% for formate production. This work provides a facile strategy for the application of glycerol upgradation in energy-saving water electrolysis systems.